CRISPR/Cas9-Mediated Gene Editing in Human iPSC-Derived Macrophage Reveals Lysosomal Acid Lipase Function in Human Macrophages—Brief Report. Issue 11 (November 2017) - Zhang, Hanrui; Shi, Jianting; Hachet, Melanie A.; Xue, Chenyi; Bauer, Robert C.; Jiang, Hongfeng; Li, Wenjun; Tohyama, Junichiro; Millar, John; Billheimer, Jeffrey; Phillips, Michael C.; Razani, Babak; et al.
Abstract : Objective—: To gain mechanistic insights into the role of LIPA (lipase A), the gene encoding LAL (lysosomal acid lipase) protein, in human macrophages. Approach and Results—: We used CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 (CRISPR–associated protein 9) technology to knock out LIPA in human induced pluripotent stem cells and then differentiate to macrophage (human-induced pluripotent stem cells–derived macrophage [IPSDM]) to explore the human macrophage LIPA loss-of-function phenotypes. LIPA was abundantly expressed in monocyte-derived macrophages and was markedly induced on IPSDM differentiation to comparable levels as in human monocyte–derived macrophage. IPSDM with knockout of LIPA ( LIPA −/− ) had barely detectable LAL enzymatic activity. Control and LIPA −/− IPSDM were loaded with [ 3 H]-cholesteryl oleate–labeled AcLDL (acetylated low-density lipoprotein) followed by efflux to apolipoprotein A-I. Efflux of liberated [ 3 H]-cholesterol to apolipoprotein A-I was abolished in LIPA −/− IPSDM, indicating deficiency in LAL-mediated lysosomal cholesteryl ester hydrolysis. In cells loaded with [ 3 H]-cholesterol–labeled AcLDL, [ 3 H]-cholesterol efflux was, however, not different between control and LIPA −/− IPSDM. ABCA1 (ATP-binding cassette, subfamily A, member 1) expression was upregulated by AcLDL loading but to a similar extent between control and LIPA −/− IPSDM. In nonlipid loaded state, LIPA −/− IPSDM had high levels of cholesteryl ester mass compared with minute amounts in control IPSDM. Yet, with AcLDL loading, overall cholesteryl ester mass was increased to similar levels in both control and LIPA −/− IPSDM. LIPA −/− did not impact lysosomal apolipoprotein-B degradation or expression of IL1B, IL6, and CCL5. Conclusions—: LIPA −/− IPSDM reveals macrophage-specific hallmarks of LIPA deficiency. CRISPR/Cas9 and IPSDM provide important tools to study human macrophage biology and more broadly for future studies of disease-associated LIPA genetic variation in human macrophages. Abstract : Supplemental Digital Content is available in the text.